Numerical Study of Bearing Strength of Infilled Concrete in Large Diameter CFST Column Reinforced by Shear Stoppers - My Pham; Ngoc-Hieu Dinh; Cong-Thuat Dang; Hoai-Chinh Truong (Designs, 2024)
Ensuring an adequate bond between the steel tube and infilled concrete interface plays an essential role in achieving composite action for concrete-filled steel tubular (CFST) columns. Thus, this study proposes a new type of large diameter CFST column where the steel tube is reinforced by shear stoppers. The bearing strength of the infilled concrete is the decisive factor in evaluating the overall working efficiency between infilled concrete and steel tube. In this paper, we use nonlinear finite element analysis (NFEA) to investigate the bearing strength of the infilled concrete concerning the ratio of the steel tube’s diameter to its thickness <semantics>(D/t)</semantics>, the number of shear stoppers <semantics><mfenced separators="|">N</mfenced></semantics>, the height of the shear stopper <semantics><mfenced separators="|">hb</mfenced></semantics>, and the concrete compressive strength (CCS) <semantics><mfenced separators="|"><msubsup>fc′</msubsup></mfenced></semantics>. Our results show that the influencing factors on the bearing strength of the infilled concrete were arranged in descending order as follows: the number of shear stoppers, the height of shear stopper, the CCS, and the <semantics>D/t</semantics> ratio. We also analyze and highlight some significant parameters related to the bearing strength of infilled concrete.